Meditation for meaning in life and happiness of older adults: A multi-city experiment of the Brahma Kumaris' Raja yoga practice - Pandya, Samta P. (Journal of religion, spirituality & aging, 2019)
This article reports on a multi-city experiment of a customized Raja yoga meditation program in enhancing the meaning in life and happiness of older adults. Participant cohort was comprised of 698 older adult followers across 10 European and African cities with an equal number in the comparison group. Results indicated that meditation positively impacted the life satisfaction and happiness of participants. Post-test outcome measure scores were higher for participants from European cities, women, middle class, retired, never married, and widowed, with good self-rated health, who regularly attended the meditation sessions and self-practiced. Participants' personal engagement through regular self-practice was the most significant predictor of higher post-test meaning in life and subjective happiness. Results imply that this specially designed Raja yoga meditation is a strong pastoral care practice that could be used with older adults with some variations based on cultural, biographical, and health profiles of participants and regular self-practice as a prerequisite.